(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explored the relationship between home numeracy practices and the development of early math skills of preschool children at Summit Integrated Laboratory Academy Inc. Specifically, it examined how different components of the home numeracy environment—such as engagement with numeracy skills, use of number books, math-related games, and real-life application activities—relate to the children’s overall math performance. Data were collected from 40 parent-child pairs using a structured survey and direct skill assessments administered to the children. Descriptive statistical analysis revealed that children demonstrated high exposure to numeracy skills and number book activities but showed low engagement in numeracy-related games and real-life applications. Despite this imbalance in exposure, all children achieved advanced levels of numeracy skills, indicating strong early math development. However, correlation analysis showed no statistically significant relationship between the overall home numeracy experience and children’s numeracy performance (r = 0.073, p = 0.656). These findings suggest that while home-based numeracy experiences contribute to children’s learning, they may not be the sole determining factor in early mathematical development. Other elements, such as preschool instruction quality, teacher support, and individual learner characteristics, may also play crucial roles. Given these results, the study recommends initiatives such as parent education and training programs, enhanced home-school partnerships, and further research using qualitative methods to explore the contextual factors that shape home numeracy practices. Understanding these dynamics is essential for developing targeted interventions that support holistic numeracy development in early childhood, particularly in the Philippine educational setting.